A backward shaping progression for wrestling - Rushall, B. S.
The diagram below illustrates the sequence of instructional progressions for learning a "double-leg / sprawl / head-whip" maneuver. Picture 1 shows the terminal position that should be attained if the skill is executed correctly. In accordance with correct pedagogical principles, each trial must be completed successfully by attaining the desired terminal position.